2023
DOI: 10.1098/rspb.2023.0638
|View full text |Cite
|
Sign up to set email alerts
|

Raptorial appendages of the Cambrian apex predatorAnomalocaris canadensisare built for soft prey and speed

Abstract: The stem-group euarthropod Anomalocaris canadensis is one of the largest Cambrian animals and is often considered the quintessential apex predator of its time. This radiodont is commonly interpreted as a demersal hunter, responsible for inflicting injuries seen in benthic trilobites. However, controversy surrounds the ability of A. canadensis to use its spinose frontal appendages to masticate or even manipulate biomineralized prey. Here, we apply a new integrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 83 publications
(152 reference statements)
0
2
0
Order By: Relevance
“… 60 A recent interesting study further suggested that radiodont euarthropods (despite being a raptorial predator of the Cambrian communities) were seemingly incapable of crushing biomineralized prey using their spinose frontal appendages. 61 These observations suggest that the impact of animal predation on the evolution of shell-bearing mollusks may have been minimal during the initial diversification of molluskan shell biomineralization in the Cambrian Terreneuvian, though predation pressure was most frequently discussed as a driving force for biomineralization.…”
Section: Discussionmentioning
confidence: 97%
“… 60 A recent interesting study further suggested that radiodont euarthropods (despite being a raptorial predator of the Cambrian communities) were seemingly incapable of crushing biomineralized prey using their spinose frontal appendages. 61 These observations suggest that the impact of animal predation on the evolution of shell-bearing mollusks may have been minimal during the initial diversification of molluskan shell biomineralization in the Cambrian Terreneuvian, though predation pressure was most frequently discussed as a driving force for biomineralization.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, in permutation 5 (Figures 4c,d and 6c,d), this might have been hydro‐dynamically advantageous during swimming. Given the prominence of these large structures, it is plausible that pterygotids somehow folded them ventrally/backward when exhibiting agility (see discussion in Bicknell, Schmidt, et al., 2023). Furthermore, regardless of being euthygnathous or klinognathous, complete flexion of joint 1 and joint 2 would have enabled the chela to approach very close to the oral region for further masticatory work of the gnathobases.…”
Section: Discussionmentioning
confidence: 99%
“…Various quantitative methods have been employed to analyze the paleoecology of Radiodonta, including hydrodynamic calculations (Usami, 2006), 3D modeling of appendages and their movement (De Vivo et al, 2021;Bicknell et al, 2023), finite element analysis (Bicknell et al, 2023), computational fluid dynamics (Bicknell et al, 2023), and geometric morphometrics of cephalic carapaces (Daley et al, 2013a;Caron and Moysiuk, 2021). The morphology of the frontal appendages allows three main predatory groups to be distinguished: raptorial predators, sediment sifters and suspension-feeders (Daley and Budd, 2010;Vinther et al, 2014;Van Roy et al, 2015;Guo et al, 2019).…”
Section: Feeding Strategymentioning
confidence: 99%
“…The raptorial predation mode was used by members of Anomalocarididae and Amplectobeluidae (Daley and Budd, 2010;Daley et al, 2013b). The appendages of Anomalocaris canadensis (Figure 4F) are many-segmented and well-articulated with short endites, enabling them to be mobile, flexible and dexterous, and making them efficient for catching macro-scale prey ranging in size from 20 to 50 mm (Daley and Budd, 2010;De Vivo et al, 2021;Bicknell et al, 2023). The pincer-shape appendage of Amplectobelua (Figure 4G) had a low degree of flexibility but could still grasp prey of relatively small sizes at around 20 mm (De Vivo et al, 2021).…”
Section: Feeding Strategymentioning
confidence: 99%
See 1 more Smart Citation